A stage of emancipation : change and progress at the Dublin Gate Theatre (Liverpool University Press, 2021)
Uncovering a wide range of marginalised histories of gender, class, language, ethnicity and sexuality, this volume shows how the Dublin Gate Theatre (est. 1928) played various emancipatory roles in Irish culture and society, both under the directorate of its founders, Hilton Edwards and Micheál mac Liammóir, but also in more recent times.